2008
DOI: 10.1159/000192466
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Major Telencephalic Pathways in an Elasmobranch, the Thornback Ray <i>Platyrhinoidis triseriata</i>

Abstract: The forebrain of elasmobranchs is well developed, and in some species the relative brain/body weight is comparable to that in mammals. However, little is known about the organization of major telencephalic pathways. We injected biotinylated dextran amines into the olfactory bulb, lateral pallium, dorsomedial pallium, and the forebrain bundles of the thornback ray, Platyrhinoidis triseriata. Secondary olfactory fibers from the bulb innervate the lateral pallium, the ventral division of the rostral telencephalon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 96 publications
1
29
1
Order By: Relevance
“…One of Prof. Nieuwenhuys' greatest works, the extraordinary threevolume set on the central nervous system of vertebrates, also includes a chapter on the central nervous system in cartilaginous fishes [Smeets, 1998] that is essential to an understanding of central nervous system organization in chondrichthyans. Finally, R. Glenn Northcutt has also contributed significantly to studies of the forebrain in chondrichthyan fishes [Northcutt, 1978[Northcutt, , 1989Hofmann and Northcutt, 2008], particularly in showing the importance of sampling brain variation among different species and recognizing adaptive patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of Prof. Nieuwenhuys' greatest works, the extraordinary threevolume set on the central nervous system of vertebrates, also includes a chapter on the central nervous system in cartilaginous fishes [Smeets, 1998] that is essential to an understanding of central nervous system organization in chondrichthyans. Finally, R. Glenn Northcutt has also contributed significantly to studies of the forebrain in chondrichthyan fishes [Northcutt, 1978[Northcutt, , 1989Hofmann and Northcutt, 2008], particularly in showing the importance of sampling brain variation among different species and recognizing adaptive patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental anatomical studies demonstrating the existence of non-olfactory connections in the telencephalon of elasmobranchs [Ebbesson and Schroeder, 1971;Schroeder and Ebbesson, 1974;Graeber et al, 1978;Luiten, 1981a, b;Smeets and Northcutt, 1987], and those revealing that only a restricted area of the telencephalon receives secondary olfactory fibers [Hofmann and Northcutt, 2008; see also Smeets, 1990Smeets, , 1998 for reviews] have been especially important, as they refuted the classic conception that elasmobranchs have a simple, exclusively olfactory telencephalon. With the improvement of immunohistochemical techniques, and the development of antibodies against diverse neuroactive substances, the complexity of the telencephalon in elasmobranchs has been increasingly revealed.…”
Section: Introductionmentioning
confidence: 99%
“…There are also differences in the presence of contralateral olfactory projections. Whereas no contralateral olfactory projections were found in the nurse shark Ginglymostoma [Ebbesson and Heimer, 1970;Ebbesson, 1972] and Raja [Smeets, 1983], such fiber tracts were observed in the catshark Scyliorhinus [Smeets, 1983], the bonnethead shark Sphyrna [Dryer and Graziadei, 1994], and the thornback guitarfish Platyrhinoidis [Hofmann and Northcutt, 2008]. In the last species, ipsilateral projections to the entopeduncular nucleus were also found.…”
Section: Olfactory Pathwaysmentioning
confidence: 86%
“…Heimer [1969] and Ebbesson and Heimer [1970] were the first to show that secondary and tertiary olfactory projections are restricted to the lateral pallium and area superficialis basalis in a nurse shark, Ginglymostoma . Later studies largely confirmed these reports, although the extent of the projections and the reported presence of crossed olfactory projections vary, depending on the species and the authors [Smeets, 1983;Dryer and Graziadei, 1994;Hofmann and Northcutt, 2008].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation